Analysis of Modular and Rhythmic Members in Design Masterpieces - MIRKHASANOV, Rustem Faritovich; IVANOVA, Elena Evgenevna; MUKHARLYAMOVA, Liliya Rashidovna; MISKICHEKOVA, Zanfira Yagsupovna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to the description of the practical and theoretical development of the formal sphere and will be useful for practitioners, theorists of design art, students, future designers. But this is impossible without extensive and solid knowledge of the objective, evolutionary development of form in the visual arts. We see one of the solutions to this problem as developed by the authors of the analytical schematic tasks presented in this article. Thus, thanks to the analysis of formal components in the creative products of well-known personalities, the student will be more ready to create their own copyright works. RESUMEN El artículo está dedicado a la descripción del desarrollo práctico y teórico de la esfera formal y será útil para profesionales, teóricos del arte del diseño, estudiantes, futuros diseñadores. Pero esto es imposible sin un conocimiento extenso y sólido del desarrollo objetivo y evolutivo de la forma en las artes visuales. Vemos una de las soluciones a este problema desarrollada por los autores de las tareas analíticas esquemáticas presentadas en este artículo. Por lo tanto, gracias al análisis de componentes formales en los productos creativos de personalidades conocidas, el estudiante estará más preparado para crear sus propios trabajos con derechos de autor.